Reducing the Prevalence of Stroke in Nigeria by Addressing Hypertension and Alcohol Use as Risk Factors - Gosal, Hitika (SFU Health Sciences Undergraduate Journal, 2023)
Due to Nigeria’s aging population, the prevalence of strokes remains a high threat for the country. Although Nigeria has focused on stroke treatment, these is a lack of preventative interventions. Management of hypertension and alcohol consumption are two modifiable risk factors that have been found to decrease the risk of strokes but are loosely regulated in Nigeria. The aim of this paper is to 1) review the measures currently in place for preventing strokes in Nigeria and, 2) propose that reduction of salt consumption and, 3) revision of alcohol consumption policies can reduce the risk of strokes in Nigeria.